Analysis of Customer Satisfaction on Wadi'ah Savings Products at Bank Financing Rakyat Syariah (BPRS) HIK Parahyangan Ciamis - Ghina Aulia Rahmah; Nila Nurochani; Mulia Amirullah (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
While achieving customer satisfaction is no easy task, it is the most common issue in every service-based business unit. Because there are many other things that can affect whether or not the level of customer satisfaction is achieved. The purpose of this study is to establish priority criteria and ascertain the extent of customer satisfaction of BPRS HIK Parahyangan Ciamis savings customers with the perception of service provider performance. BPRS HIK Parahyangan Ciamis must prioritize improvement by utilizing the Customer Satisfaction Index (CSI) method to determine the level of customer satisfaction and the Importance Performance Analysis (IPA) method to determine the importance of each service attribute. Employee attributes provide flexibility to save which can be taken at any time with an average value of 4.77, according to the interest rate of BPRS HIK Parahyangan Ciamis customers which is calculated using the Importance Performance Analysis (IPA) method. With an average value of 4.42, the Banking Transaction Room Cleanliness attribute is considered to have the highest level of performance in terms of company performance. With a Customer Satisfaction Index (CSI) score of 83.73 percent, the calculation results show that respondents and customers are satisfied with the performance of the service provider.